Recommendations on the procedure for determining the interchangeability of medicinal products - B. K. Romanov; N. D. Bunyatyan; Yu. V. Olefir; V. P. Bondarev; A. B. Prokofyev; R. I. Yagudina; R. N. Alyautdin; E. L. Kovaleva; A. P. Pereverzev; K. E. Zatolochina; A. S. Kazakov; A. V. Komratov; et al. (Регуляторные исследования и экспертиза лекарственных средств, 2018)
The authors developed and presented recommendations on the procedure for determining the interchangeability of medicinal products. Interchangeability of drugs determined at the state registration of the medicinal product or when amendments to the documents contained in the registration dossier for already medicinal product. Recommended by the authors of the sequence of procedures for determining the interchangeability of drugs includes four successive stages. The conformity assessment of generic medicinal product reference drug proposed by six parameters specified in the Federal Law N 429-FZ, in sequence («Аlgorithm for the assessment of interchangeability»).